Use of the Vineland Adaptive Behavior Scale in the assessment of intellectually disabled complainants in sexual abuse cases in the Western Cape - Douglas, Gillian Kathleen (Stellenbosch : Stellenbosch University, 2017)
Thesis (Ph.D)--Stellenbosch University, 2017.